Degradation of Nitrobenzene by Persulfate Activated with Zero-valent Iron - Chung, T.V.; Anh, T.Q.; Phung, D.Q.; Luong, T.D. (Asian Journal of Chemistry, 2011)
The properties of zero-valent iron is useful in remediation of aromatic nitro compounds by reducing them to convert onto the amino products which may also lead to oxidize or mineralize them with the presence of persulfate anion (S2O82–). In practice, with the zero-valent iron, persulfate anion (E0 = 2.01 V) may be activated to produce free sulfate radical (SO4–•) with the higher standard reduction potential (E0 = 2.60 V). It is an active reagent for the mineralization of nitrobenzene in the studied samples. The activation process of persulfate in solution with zerovalent iron to produce SO4–•, may be implemented by the following pathways: In the heterogeneous system the activation reaction was implemented on iron surface: Fe(0) + 2S2O82– ® Fe2+ + 2SO4–• + 2SO42–, In homogeneous case, the activation process was implemented in solution: Fe2+ + S2O82–• ® Fe3+ + SO4–• + SO42– In the studied system zero-valent iron is a source producing Fe2+ to keep the activation of persulfate anion. The free sulfate radical formed in situ oxidizes nitrobenzene causing the decrease of the total organic carbon in the samples. The experimental data have shown that the nitrobenzene concentration of 80 mg/L in the system consisting of 500 mg/L of Na2S2O8 and 1 g/L of zerovalent iron, pH = 5, the efficiency of nitrobenzene mineralization may reach for 98 % for 40 min. The nitrobenzene was first reduced with zero-valent iron then transported for the further oxidation with free sulfate radical, the mineralization nitrobenzene may reach for 95 % for 0.5 h. This means that amine products are easily oxidized than its nitro compounds. The obtained experimental data have suggested that the reduction of nitrobenzene by zero-valent iron may be combined with the oxidation process with persulfate activated with zero-valent iron to enhance the nitrobenzene degradation efficiency and the efficiency of zero-valent iron used. The factors such as ratios of persulfate/zero-valent iron/ nitrobenzene, pH, the addition of Fe2+ influencing on the efficiency of nitrobenzene mineralization have been investigated.